New tricks for an old drug. (November 2018) - Nelson, Barbara; Kremer, Daniel; Lyssiotis, Costas
The prodrug dimethyloxalylglycine (DMOG) is a well-known tool compound used to study hypoxia. New findings reveal that DMOG also inhibits glutamine metabolism and can be exploited to selectively kill some cancer cells, highlighting important caveats when using DMOG for hypoxia studies.